MEKANISME LONGSOR AKIBAT INFILTRASI DARI GENANGAN AIR (STUDI KASUS LONGSOR DI LAHAT, SUMATERA SELATAN) - Rokhmat Hidayat; I Putu Eddy Purna Wijaya; Moh. Dedi Munir (Pusat Litbang Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2023)
ABSTRACTThe landslide occurred in the Lahat-Pagaralam road section on February 2, 2019. The landslide caused the road to be cut off for several days. The disconnection of roads triggered disruption of economic activity. The landslide might be caused by a puddle of rainwater seeping into the road. Several cases of landslide triggered by ponding water also occurred on the Kuningan-Tasikmalaya road in Cikijing Tasikmalaya, and on the Gempol-Pandaan toll road in East Java. The purpose of this study, therefore, was to determine the safety criteria based on the results of safety factors, the amount of seepage, and the pattern of collapse of the road, thus the incidents can be anticipated and are expected not to occur in other locations. The research method begins with field survey, depicting the geometry of the road, and collecting geotechnical data for landslide locations. Slope stability modeling due to water infiltration was processed using the SLOPE-W program. The results of road slope stability modeling at the landslide location show that when there is a 1m inundation, the slope stability value of factor of safety (FS) is 0.916 (a condition prone to landslides). The direction of flow comes from right to left, the right is a small slope and the left slope is a river bank. The difference in water level on the right and left of the road causes water to seep into the soil layer and cause the groundwater level to rise. The occurrence of water flow along the soil pile, causing water to fill the gaps between soil. The value of the slope stability number decreases due to water infiltration into the soil, resulting in landslides. SF value decreases from 0.916 to 0.887 when the inundation height increases from 1 m to 5 m. We concluded that the presence of water ponding around the road strongly suspected to be the cause of landslides. It is necessary to prevent ponding with a drainage system, so that it will not affect to the stability of the road.Keywords: landslide, slope stability, water infiltration, water ponding, drainage. ABSTRAKTelah terjadi longsor pada ruas jalan Lahat-Pagaralam pada 2 Februari 2019. Longsoran menyebabkan jalan terputus selama beberapa hari. Terputusnya ruas jalan menyebabkan gangguan aktivitas ekonomi. Longsor diduga disebabkan adanya genangan air hujan yang meresap ke badan jalan. Beberapa kasus longsor yang dipicu oleh genangan air juga terjadi pada ruas jalan Kuningan-Tasikmalaya di Cikijing Tasikmalaya, dan pada ruas tol Gempol-Pandaan Jawa Timur. Tujuan dari penelitian ini adalah untuk mengetahui kriteria keamanan lereng berdasarkan hasil analisis yang berupa angka faktor keamanan dan jumlah debit rembesan serta pola runtuh/longsor pada badan jalan, sehingga kejadian seperti ini bisa diantisipasi dan diharapkan tidak terjadi di lokasi lain. Metode penelitian diawali dengan survei lapangan, penggambaran geometri badan jalan, dan pengumpulan data geotek tanah lokasi longsor. Pemodelan stabilitas lereng akibat infiltasi air dilakukan dengan progran SLOPE-W. Hasil pemodelan stabilitas lereng jalan di lokasi longsor menunjukkan bahwa saat terjadi genangan 1m maka nilai stabilitas lereng (factor of safety FS) adalah 0,916 (kondisi rawan terjadi longsor). Arah aliran datang dari kanan ke kiri badan jalan, lereng kanan berupa alur kecil dan lereng kiri merupakan tebing sungai. Perbedaan tinggi muka air di kanan dan kiri menyebabkan air merembes masuk ke dalam lapisan tanah dan menjadikan muka air tanah naik. Terjadinya aliran air sepanjang timbunan tanah, mengakibatkan air mengisi celah antar butir. Nilai angka stablitas lereng turun akibat infiltrasi air ke dalam tanah, sehingga terjadi longsor. Nilai SF turun dari 0,916 menjadi 0,877 ketika tinggi genangan naik dari 1 m menjadi 5 m. Kajian ini menyimpulkan bahwa keberadaan genangan air di sekitar jalan diduga kuat menjadi penyebab terjadinya longsoran. Oleh karena itu, perlu dicegah terjadinya genangan dengan sistem drainase sehingga tidak mempengaruhi stabilitas lereng jalan.Kata kunci: longsor, stabilitas lereng, infiltasi air, genangan air, drainase